The Vertical Mosaic Revisited - Helmes-Hayes, Richard C.; Curtis, James E. (Heritage, 1998)
When The Vertical Mosaic first appeared in 1965, it became an instant classic. Its key message was that Canada was not the classless democracy it fancied itself to be. In fact, Canada was a highly inegalitarian society comprising a 'vertical mosaic' of distinct classes and ethnic groups. This collection of papers by five of Canada's top sociologists subjects John Porter's landmark study to renewed scrutiny and traces the dramatic changes since Porter's time - both in Canadian society and in the agenda of Canadian sociology. Based on papers written for a conference held in commemoration of the thirtieth anniversary of The Vertical Mosaic's publication, the five essays revisit the central themes of the original work, including gender and race inequality; citizenship and social justice; and class, power, and ethnicity from the viewpoint of political economy. An introduction by the editors provides a historical biography of Porter and discusses his influence on Canadian sociology. --Publisher's description. Contents: Power, ethnicity, and class: Reflections thirty years after The vertical mosaic / Wallace Clement -- Ethnicity and race in social organization: Recent developments in Canadian society / Raymond Breton -- Missing women: A feminist perspective on The vertical mosaic / Pat Armstrong -- Three decades of elite research in Canada: John Porter's unfulfilled legacy / Michael Ornstein -- Social justice, social citizenship, and the welfare state, 1965-1995: Canada comparative context / Julia S. O'Connor.
Keywords: Canada; Canada Conditions sociales 1945-; Canada Social conditions 1945-; Classes sociales Canada; Porter, John, 1921-1979; Pouvoir (Sciences sociales) Canada; Power (Social sciences); Power (Social sciences) Canada; Since 1945; Social classes; Social classes Canada; Social conditions